BENEFITS OF SOCIAL DANCING AMONG OLDER ADULTS WITH COGNITIVE DECLINE AND NEURODEGENERATIVE DISEASES: A SYSTEMATIC REVIEW - Anna Opalińska; Paula Folta; Cezary Lubas; Joanna Kłosowska; Kacper Szeląg; Karolina Błądzińska; Maciej Błądziński; Małgorzata Zach; Piotr Świerczek; Antoni Kujawski (International Journal of Innovative Technologies in Social Science, 2025)
Research objectives: This review aims to synthesize the current evidence on social dancing for older adults, with particular emphasis on its therapeutic benefits for individuals with Parkinson’s disease.Methods: A literature review was gathered using PubMed and Google Scholar, emphasizing papers published in the last five years. The search included the keywords ‘dance’, ‘cognitive function’, and ‘physical activity’.Key findings and conclusions: The expansion and ongoing advancement of modern medicine correlates with the increase in the older adult population. As a result, cognitive decline has become one of the major health problems associated with advanced age. Nearly 50% of individuals over 85 years are suffering from dementia and related neurodegenerative diseases. Extending healthy life expectancy has become a cardinal priority for public-health systems and biomedical research alike. Despite ongoing efforts, the search for low-cost, scalable interventions that can simultaneously preserve neural function, functional mobility, and psychosocial well-being remains incomplete. Studies show that dance-based exercise is a promising candidate. Accumulated findings indicate that dance constitutes a biologically and psychosocially potent intervention, simultaneously enhancing cardiovascular efficiency, maintaining neuromuscular integrity, promoting neuroplastic remodelling, and improving emotional well-being.